Konsep Dan Pengelolaan Kolam Renang Berbasis Nilai-Nilai Syariah : Studi Kasus Telaga Alam Boyolali - Alam, Azhar; Zulkifli, Muhammad; Nurrahman, Aditya (Halal Center ITS, 2023)
This study aims to find out how the concept and management of Telaga Alam swimming pools and how Telaga Alam swimming pools apply the DSN-MUI fatwa. The research method used is qualitative and descriptive. The types of data used are primary and secondary data. Primary data were obtained through interviews with the pool manager and one pool employee and three swimming pool visitors. The secondary data was obtained through literature related to the concept and management of swimming pools. The results of this study indicate that the concept and management of the Telaga Alam swimming pool has several facilities in it such as a separate swimming pool for men and women, a canteen that provides halal food and drinks, and other facilities such as: pavilion, and a therapy pool. fish. However, there needs to be an improvement in the management of the Telaga Alam swimming pool to meet halal aspects, as regulated in the DSN-MUI for example the separation of fish therapy pools between men and women as well as providing proper worship facilities. Thus, this research is expected to provide an overview of the concept and management of halal tourism in the Telaga Alam swimming pool area or in other areas in accordance with Sharia or the DSN-MUI fatwa.